-13+p=-10

Simple and best practice solution for -13+p=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13+p=-10 equation:



-13+p=-10
We move all terms to the left:
-13+p-(-10)=0
We add all the numbers together, and all the variables
p-3=0
We move all terms containing p to the left, all other terms to the right
p=3

You can always share this solution

See similar equations:

| 1.5x-(6)=7.5 | | 7x+4-2x=10x+16 | | 2x?3+4x=29 | | -x-20=6x+1 | | -4x-(18)=22 | | a+7-3(2a+5)=-2(a-15)-5 | | X+19=2x-20;-1 | | x/5-3x+7/10=1 | | 3u+64=11u | | f(2)=1.5(2)+1 | | 8(x-3)=8x+40 | | 2x-14+2x=4(4x-5)+2 | | 3=1,5b | | | | | | 64=48/x | | 56-8x=32 | | 8x-34=5×+2 | | 5t²-40t-9=0 | | 4/28=7/x | | 6x+87=14x+47 | | 18x2-3x+24x-4=0 | | 130+150+2d=360 | | 400=0.3*x | | 8+2m=–8+m | | p(10)=2500(1.019)^10 | | 4x^2+68x+864=0 | | 5+(4(y)=24 | | p(9)=1500(1.022)^9 | | 0.25=3^m | | 0.25=3m | | 7n+4=3n-36 | | x-2(0)+7=0 |

Equations solver categories